A ditopic calix[4]pyrrole amide derivative: highlighting the importance of fundamental studies and the use of NaPh4B as additive in the design and applications of mercury(ii) ion selective electrodes1. Issue 24 (28th June 2015) - de Namor, Angela F. Danil; El Gamouz, Abdelaziz; Alharthi, Salman; Al Hakawati, Nawal; Varcoe, John R.
<x xml:space="preserve">Abstract</x> A ditopic calix[4]pyrrole amide based ion selective electrode and its applications are first reported. Sodium tetraphenylboron currently used as additive in Hg ISE is by itself a sensor for mercury(ii).